X= -b plus or minus the square root of (b)^2 – 4 (a)(c), all over 2(a)
Just substitute them into the equation: a= 1 because 1x^2 is 1 (always use the number in front of the x^2 for a).
b= -1 because -1x (always use the number in front of x for b)
c= -1 because -1 is the number that stands alone (always use this for c)
Now just substitute the numbers into the equation and solve it, the answer should come out to be: 1 plus or minus the square root of 5 over 2
Good luck!
REMEMBER: a negative times a negative makes a positive so when u substitute -1 in for b at the beginning of the equations the –b should be –(-1) which makes a positive 1. The rule applies for all algebra.
2006-12-30 10:48:20
·
answer #1
·
answered by JMan 3
·
1⤊
0⤋
You want to use the quadratic formula to solve it.
The equation is in the form ax^2 + bx + c = 0
and the quadratic equation is
[-b +or- root(b^2 - 4ac)] / 2a
First you must find what a,b and c are in your equation. Since there is only one X^2, a=1. There is a -1 in front of the x for your -x so b=-1. C = -1 obviously. Now all you have to do is plug a,b, and c into the quadratic equation.
[-(-1) +or- squareroot((-1)^2 -4(1)(-1))]/2(1)
Simplify
[1 +or- squareroot(5)] / 2
So your answer will be:
.5 + root(5)/2
or
.5 - root(5)/2
2006-12-30 19:01:55
·
answer #2
·
answered by Roman Soldier 5
·
0⤊
0⤋
quadratic formula is x = -b + or - sqr(b^2 - 4ac)/2a
your equation x^2 - x - 1 = 0 is in the form of
ax^2 + bx + c = 0 with a and b = 1 because a variable without a coefficient the coefficient is assumed to be 1 and c is the lone integer, the =0 is to be ignored.
you just plug in your variables and solve for x twice
2006-12-30 19:28:55
·
answer #3
·
answered by ikeman32 6
·
0⤊
0⤋
X^2-x-1=0
x=(1+/-â(1+4))/2
x=(1+â5)/2 (1-â5)/2
2006-12-30 19:10:49
·
answer #4
·
answered by yupchagee 7
·
0⤊
0⤋
You can use the quadratic equation to solve this. It is: x = -b =/- [sqr(b^2-4ac)]/2a. In your problem then, a = 1, b = -1, and c -1. Plug these in and solve.
2006-12-30 20:07:21
·
answer #5
·
answered by flyfisher_20750 3
·
0⤊
0⤋
What don't you get?
1 ± Sq Root ( 5) ÷ 2 = 1.618 or -0.61803
2006-12-30 18:37:47
·
answer #6
·
answered by jaden404 4
·
0⤊
0⤋
what are you asking about? do you want to know if it is or what the answer is?
i think the answer is one plus or minus the square root of 5 all over two. i think.
2006-12-30 18:36:50
·
answer #7
·
answered by HansonFan 6
·
0⤊
0⤋
isn't this YOUR homework? and isn't that the same exact polynomial that they use to explain the quadratic formula, except with subtractions instead of additions?
2006-12-30 18:36:39
·
answer #8
·
answered by somebody super cool 3
·
1⤊
0⤋
yes it is. quadratic means that there is an x^2 in the equation
2006-12-30 18:36:31
·
answer #9
·
answered by mojo2093@sbcglobal.net 5
·
0⤊
0⤋
hope the website helps
2006-12-30 18:37:26
·
answer #10
·
answered by shhh secret 2
·
0⤊
0⤋